Research on multi-energy cooperative participation of grid frequency inertia response control strategy for energy storage type doubly-fed wind turbine considering wind speed disturbance - Sun, Dongyang; Zhao, Fanqi; Guo, Yifen; Meng, Fanyi; Zheng, Wenyuan; Yu, Jixuan (Frontiers in Energy Research, 2023)
With the proposal of carbon peaking and carbon neutralization, the penetration rate of wind power generation continues to increase. This paper focuses on the problem that doubly fed induction wind turbines are vulnerable to input "source" disturbances and have weak frequency modulation ability, which reduces the stability of the power grid. By comparing the advantages and disadvantages of different wind turbines and energy storage systems, this paper determines the structural model energy storage system embedded in doubly fed wind power generation system. According to the mathematical model and operating characteristics of doubly fed wind power generator, the power working range of power generation system and super capacitor of energy storage doubly fed wind power system under different rotating speeds and working conditions is proposed. The ability of super capacitor energy storage and releasing rotor kinetic energy to provide inertia response power and energy is compared, and the feasibility of multi-energy coordinated inertia response is analyzed. Based on the inertia time constant of conventional synchronous generator set, the inertia time constant and actual inertia constant of energy storage doubly fed wind power generation system under variable wind speed are defined. Considering the influence of wind speed change and the protection of unit speed, it is necessary to estimate the captured mechanical power. An extended state observer is used to estimate the change of captured mechanical power caused by the change of wind speed, and the results are applied to the design of frequency modulation control strategy. A control strategy for doubly fed induction generator with super capacitor to participate in power grid frequency regulation is designed by using wind turbine working condition, super capacitor state of charge and estimation of captured mechanical power variation as optimization constraints. Finally, considering the aggregation of wind power and the difference of the state of charge during the operation of distributed energy storage, the 3*3*3 wind farm model is established using Matlab/Simulink simulation software. The feasibility and advantages of the frequency modulation control strategy proposed in this paper are verified by building a power grid frequency modulation simulation involving wind farms and traditional generators.